Proceedings of the Fifteenth International Conference on Tangible, Embedded, and Embodied Interaction 2021
DOI: 10.1145/3430524.3440654
|View full text |Cite
|
Sign up to set email alerts
|

Flowcuits: Crafting Tangible and Interactive Electrical Components with Liquid Metal Circuits

Abstract: We present Flowcuits, a DIY fabrication method to prototype tangible, interactive and functional electrical components by manipulating liquid metals. The prototypes afford both physical and visual interactions to demonstrate the inner working mechanics of fundamental electronic elements, which enables tangible and playful learning. The fabrication process follows simple imprinting and sealing of fluidic circuits with a 3D-printed stamp on an accessible moldable-substrates such as 'Blu Tack'. Utilizing conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…However, this process has several disadvantages: removing unnecessary material after cutting is cumbersome and time-consuming, and thin traces can be damaged when removing the surrounding material [26]. In addition to the above, gold foil [25,29], a water-transferring technique [7], 3D printing of conductive filaments [10,28,30,35], conductive material plated nylon fabric [13], carbon-coated paper [42], and liquid metal [32] have been used for circuit fabrication.…”
Section: Fabrication Of Customized Electronicsmentioning
confidence: 99%
“…However, this process has several disadvantages: removing unnecessary material after cutting is cumbersome and time-consuming, and thin traces can be damaged when removing the surrounding material [26]. In addition to the above, gold foil [25,29], a water-transferring technique [7], 3D printing of conductive filaments [10,28,30,35], conductive material plated nylon fabric [13], carbon-coated paper [42], and liquid metal [32] have been used for circuit fabrication.…”
Section: Fabrication Of Customized Electronicsmentioning
confidence: 99%
“…For example, Swaminathan et al demonstrated a technique to fabricate conductive traces while keeping the object mechanically strong for heavy use [66]. In addition to solid conductive traces, recent work has adopted conductive liquids for fabricating circuits using a 3D printed stamp as the circuit mold [69]. Beyond rigid objects, existing works also show the feasibility of embedding conductive traces or electronics for 3D printed flexible objects, such as conductive fabrics [43], electrospun textiles [46], using foldable structures [42,78], or the flexible TPU (Thermoplastic Polyurethane) material with silver inks (i.e., AgTPU) [70].…”
Section: Embedding Objects With 3d Printsmentioning
confidence: 99%
“…For example, Stretchable and Soft Electronics [1] uses liquid metal to create shape-confgurable circuits through guiding electrically actuated gallium-based liquids on pre-fabricated paths. Similarly, Flowcuits [10] uses blue-tac as a re-usable material to engrave guiding circuit paths for liquid metals to fow on. These direct means, however, require physical intervention, which is sub-optimal for remote learning experiences and collaborations.…”
Section: Introductionmentioning
confidence: 99%